Teacher’s Perception of Using Quizizz To Enhance Student’s Motivation In Learning English In Junior High School - Batubara, Afrohul Fadhillah; Lubis, Yani (ITScience (Information Technology and Science), 2025)
Most students found English learning at school less interesting because it still used one-way and teacher-centered methods. Therefore, this study explored how using Quizizz could enhance students' motivation in learning English at the junior high school level. Traditional learning methods, such as lectures and practice questions without interactive media support, made students feel bored and less motivated to learn. To overcome these problems, the use of digital media was considered one solution. Quizizz is a digital learning platform accessed via smartphones and an internet connection, providing interactive features such as multiple-choice Quizizz zes, real-time feedback, points, music, and leaderboards. These elements are designed to turn conventional learning into a fun, game-like experience that promotes competition and engagement among students. Unlike traditional methods that rely on passive listening and textbook exercises, Quizizz offers a more dynamic approach that encourages active participation. Based on this potential, the present study aimed to examine how using Quizizz could enhance students' motivation and improve their learning outcomes in English subjects, especially in a junior high school context where maintaining student interest is a key challenge. This study employed a descriptive qualitative approach. Data were collected through questionnaires and semi-structured interviews. The participants in this study consisted of four English teachers and thirty-one grade 7 students. Data analysis was conducted by reducing, presenting, and drawing conclusions from the collected data. The results showed that the use of Quizizz had a positive impact on increasing students' motivation and learning outcomes. The findings suggested that integrating technology in learning could be an innovative solution for improving the quality of English education in schools.